Biomarkers for the diagnosis of acute cellular rejection in liver transplant recipients: A review. Issue 2 (27th November 2012) - Verhelst, Xavier P.D.; Troisi, Roberto I.; Colle, Isabelle; Geerts, Anja; van Vlierberghe, Hans
<x xml:space="preserve">Abstract</x> The gold standard for the diagnosis of acute cellular rejection (ACR) is a liver biopsy. The quest for an alternative non‐invasive biomarkers has been long and is ongoing. However, an efficient and useful biomarker has not been developed yet. In this manuscript, we review all possible candidate biomarkers that have been studied in recent years, starting with cytokines and ending with an overview of different newly discovered "omics". Promising paths are being explored but a valid non‐invasive biomarker has not been discovered yet.